Nutritional Quality of Soybean Seeds Relative to Canopy Portion - L. H. Moro Rosso; W. D. Carciochi; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2019)
Soybean [Glycine max(L.) Merr.] seed quality (nutritional composition) is affected by genetic × environment × management (G × E × M) interactions. Even at the plant level, where differences might not be largely apparent, seed quality is known to change. This study aims to 1) compare seed yield and nutritional quality within the vertical profile of soybean plant canopy, and 2) explore potential interactions for different genotypes. A field experiment was conducted in Manhattan, KS, during the 2018 growing season. Treatments were composed by six genotypes and evaluated at four canopy portions: upper, middle, and lower sections of the main stem and branches. The study was set in a complete randomized block design with three replications. Seed yield and seed size were determined at physiological maturity, as well as seed quality (e.g., protein and oil concentrations). For seed yield, the contribution of the branches was directly affected by the genotype, while the other portions presented a similar yield across genotypes. Seed size was greater in the upper and middle portions of the plant canopy, and seed size of the branches was always comparable to the average of the main stem sections. Overall, oil concentration was lower in branches and did not differ along the sections of the main stem. On the other hand, the protein concentration was greater in the upper portion of the plant. Further research should explore seed quality responsiveness to the timing of pod-setting and seed-filling within the soybean canopy.
Keywords: Glycine max; genotype; protein; oil